Low-Temperature Oxidation of Methylene Bridge Bond in Coal by Model Compound - Tang, Yibo; Li, Zenghua; C. Tien, Jerry; Yin, Wenxuan; Ma, Dongjuan (Asian Journal of Chemistry, 2014)
In order to find out characteristics of active structures in coal at early phase of oxidation, diphenylmethane was adopted as the model compound to study the oxidation properties of bridge bond (methylene) in coal with low-temperature experimental condition (293 K-423 K), according to structure of molecular coal. Mean while, the generated oxidation products under different reaction conditions were analyzed qualitatively via FTIR spectrometer and GC-MS. The results show that the new structures which involve C-O, C=O, Ar-O and Ar-OH are constantly generated with temperature rise in the process of low-temperature oxidation of diphenylmethane, especially after the 393 K. Besides, the phenols, benzaldehyde, diphenylmethanone, phenyl benzoate, 2-benzyl phenols and 2-phenolic-diphenylmethanone were detected in oxidation products, which demonstrated this oxidation is a multi-step reaction. Meantime, the substitution between O and H is more easily occurs in -CH2- than in benzene ring. The temperature and time are major factors which affecting low-temperature oxidation of diphenylmethane. In conclusion, this study provides reference for explaining and controlling the low-temperature oxidation of coal from chemical perspective.